Pelaksanaan Program Larasita Dalam Penertiban Administrasi Pertanahan - Dewanto, Ahmad Rizki (Jurnal Administrasi Publik, 2014)
Abstract: The Implementation of LARASITA Program In The Restructuring Of Land Administration. (Study at National Land Agency of Malang District) Many lands are uncertified in the region of Malang District. Great distance to afford BPN Office of Malang District makes the community to hesitate themselves from administering their land. The objective of research is to describe the implementation of LARASITA program in the restructuring of land administration at BPN in delivering the service to the community and to analyze the supporting and constraining factors. Research type is descriptive with qualitative approach. The description of the implementation of LARASITA Program in this research is focused on the matters related to land certification service which include: the regulation, the authority and responsibility of the implementing organization, the procedure of certificate making service, the document of administration, and the factors supporting and constraining the implementation of program. Result of research indicates that LARASITA Program is a progressive step by BPN of Malang District to facilitate the administration of land certificate for the community in the remote area. Keywords: land, implementation and program Abstrak: Pelaksanaan Program LARASITA Dalam Penertiban Administrasi Pertanahan (Studi di Badan Pertanahan Nasional Kabupaten Malang). Banyaknya tanah-tanah yang belum tersertifikat di wilayah Kabupaten Malang dan jauhnya kantor BPN Kabupaten Malang membuat banyak masyarakat enggan untuk mengurus administrasi tanah mereka. Tujuan penelitian ini adalah untuk menggambarkan pelaksanaan program LARASITA dalam penertiban administrasi pertanahan di BPN dalam memberikan pelayanannya kepada masyarakat dan menganalisis faktor pendukung dan penghambat. Jenis penelitian ini adalah deskriptif dengan pendekatan kualitatif. Gambaran Pelaksanaan program LARASITA dalam penelitian ini difokuskan pada pelayanan sertifikasi tanah meliputi: peraturan yang dipakai, wewenang dan tanggung jawab organisasi pelaksana, prosedur pelayanan pembuatan sertifikat, dokumen administrasi, serta faktor pendukung dan penghambat pelaksanaan program. Hasil penelitian menunjukkan bahwa Program LARASITA merupakan suatu langkah maju BPN Kabupaten Malang dalam dalam mempermudah pengurusan sertifakat bagi masyarakat yang berada di daerah terpencil Kata kunci: pertanahan, implementasi, dan program